Bonding of Y-TZP to Dentin: Effects of Y-TZP Surface Conditioning, Resin Cement Type, and Aging - Bottino, M. A. [UNESP]; Bergoli, C. [UNESP]; Lima, E. G. [UNESP]; Marocho, S. M. S. [UNESP]; Souza, R. O.; Valandro, L. F. (Operative Dentistry Inc, 2014)
Purpose: To evaluate the effects of two surface treatments, aging, and two resin cements on shear bond strength between dentin and yttrium-stabilized tetragonal zirconia polycrystal ceramic (Y-TZP).Materials and Methods: Eighty human molars were embedded in acrylic resin and sectioned 3 mm below the occlusal plane. These teeth and 80 cylindrical Y-TZP specimens (height, 4 mm; diameter, 3.4 mm) were divided into eight groups (n=10) using the following factors: Y-TZP surface treatment (Vi: low-fusing porcelain [vitrification] + hydrofluoric acid etching + silanization or Si: tribochemical silicatization); cementation strategies (PF: Pan avia or CC: Clearfil); and storage (nonaging or aging). Bonding surfaces of 40 Y-TZP specimens received Vi treatment, and the rest received Si treatment. Half of the ceramic-tooth assemblies were cemented with Panavia, the rest with Clearfil. Shear tests were executed using 0.4-mm-thick wire at 0.5 mm/min. Data were analyzed by three-way analysis of variance and Tukey test (alpha=0.05). Fractures were analyzed.Results: Y-TZP surface treatments did not affect bond strength (p=0.762, Vi = Si), while resin cements (p<0.001, Panavia > Clearfil) and aging (p=0.006, nonaging > aging) showed a significant effect. Most failures were in adhesive at dentin-cement interfaces; no failure occurred between zirconia and cement.Conclusion: When Y-TZP ceramic is bonded to dentin, the weakest interface is that between dentin and resin cement. The resin cement/Y-TZP interface was less susceptible to failures, owing to Y-TZP surface treatments.